Associations of sleep and female sexual function: good sleep quality matters. Issue 6 (June 2021) - Kling, Juliana M.; Kapoor, Ekta; Mara, Kristin; Faubion, Stephanie S.
Abstract: Objective: To evaluate associations between sleep and female sexual function. Methods: A cross-sectional analysis from the Data Registry on Experiences of Aging, Menopause and Sexuality (DREAMS) was performed using questionnaires in women presenting for menopause or sexual health consult at Mayo Clinic from December, 2016 to September, 2019. Female Sexual Function Index (FSFI), Female Sexual Distress Scale-Revised (FSDS-R), and the Pittsburgh Sleep Quality Index (PSQI) assessed sexual function and sleep parameters, respectively. Associations between sleep quality (PSQI score ≥ 5 poor sleep quality), sleep durations (< 5 h, 5-6 h, 6-7 h, > 7 h) and female sexual dysfunction (FSFI ⩽ 26.55 and FSDS-R ≥ 11) were evaluated utilizing a multivariable logistic model adjusting for multiple factors. A secondary analysis evaluated sleep quality by sexual activity and also included sexually inactive women. Results: A total of 3, 433 women were included (mean age 53). Sexually active women ( N  = 2, 487; 72.4%) were included in the primary analysis; 75% had poor sleep quality, and 54% met criteria for female sexual dysfunction. On multivariable analysis, women with poor sleep quality were 1.48 times more likely to report female sexual dysfunction (95% CI 1.21-1.80, P  < 0.001). Of women who reported sleeping < 5 hours nightly, 63.3% had female sexual dysfunction, and their Female Sexual Function Index total and domain scores were significantly lower than women sleeping > 7 hours nightly ( P  = 0.004); however, this was not statistically significant in multivariable analysis. Sexually active women were more likely to report good sleep quality compared with sexually inactive women (25.3% vs 20.5%, P  = 0.003). Conclusions: Poor sleep quality, but not sleep duration, was associated with greater odds of female sexual dysfunction. Good sleep quality was linked to sexual activity. In addition to its myriad effects on health, poor sleep quality is associated with female sexual dysfunction. N/A: Video Summary: http://links.lww.com/MENO/A714 . Abstract : Supplemental Digital Content is available in the text